Gambling and Comovement - Kumar, Alok; Page, Jeremy K.; Spalt, Oliver G. (Journal of Financial and Quantitative Analysis, 2016)
Abstract This study shows that correlated trading by gambling-motivated investors generates excess return comovement among stocks with lottery features. Lottery-like stocks comove strongly with one another, and this return comovement is strongest among lottery stocks located in regions where investors exhibit stronger gambling propensity. Looking directly at investor trades, we find that investors with a greater propensity to gamble trade lottery-like stocks more actively and that those trades are more strongly correlated. Finally, we demonstrate that time variation in general gambling enthusiasm and income shocks from fluctuating economic conditions induce a systematic component in investors’ demand for lottery-like stocks.